Serological biomarkers predict immune-related adverse events and clinical benefit in patients with advanced gastrointestinal cancers - Wang, Yanni; Zou, Jianling; Li, Yun; Jiao, Xi; Wang, Yujiao; Zhuo, Na; Gao, Mengting; Gong, Jifang; Li, Jian; Zhang, Xiaotian; Wang, Xicheng; Peng, Zhi; et al. (Frontiers in Immunology, 2022)
Background: Immune checkpoint inhibitors (ICIs) have dramatically improved survival in advanced gastrointestinal (GI) cancer patients, but also resulted in immune-related adverse events (irAEs). This study aimed to evaluate serological biomarkers of irAEs and treatment response in GI cancer patients. Patients and methods: Metastatic GI cancer patients were enrolled between August 1, 2015, and July 31, 2017. Serum samples were collected at baseline, and a panel of 59 serum biomarkers was tested. The occurrence of irAEs was analyzed, and serological biomarker expression was correlated with irAE incidence and prognosis. Results: Fifty-one patients were enrolled, of whom 47.1% (24/51) were diagnosed with irAEs, including 4 patients (7.8%) with grade 3-5 irAEs. The most common irAE was thyroiditis (9/51, 17.6%), followed by colitis (7/51, 13.7%). The expression of CD28 (P = 0.042), IL-4 (P = 0.033), IL-15 (P = 0.024) and PD-L1 (P = 0.018) was significantly elevated in patients with grade 3-5 irAEs. For organ-specific irAEs, IL-6 levels were higher in patients with thyroiditis and colitis, while IL-22 and SCF levels were higher in patients with colitis. Increased IL-1α, IL-21, LIF, and PIGF-1 levels were significantly associated with myositis incidence, while the serum levels of six cytokines (BTLA, GM-CSF, IL-4, PD-1, PD-L1 and TIM-3) were higher in patients with rash. Prognostic analysis showed that patients with irAEs had better tumor response (P = 0.029), improved PFS (median survival: undefined vs. 2.1 months, P = 0.002), and extended OS (median survival: undefined vs. 4.3 months, P = 0.003). The prognostic value of irAEs was only significant in patients who received anti-PD-1 inhibitors, but not in those who received anti-PD-L1 inhibitors. Besides, elevated BTLA (median OS: not reached vs. 7 months; P = 0.0168) and PD-1 (median OS: not reached vs. 7 months; P = 0.0223) concentrations were associated with longer OS. Conclusions: Serological proteins are promising markers for predicting immune-related toxicity and prognosis in GI cancer patients. Organ-specific irAEs have various cytokine profiles. Although further validation is needed before clinical application, this study provided a direction for identifying patients at risk for irAEs, and guiding patient selection for ICI therapy.